Mechanical properties of kenaf fibre reinforced polymer composite: A review. (1st February 2015) - Saba, N.; Paridah, M.T.; Jawaid, M.
Highlights: Kenaf fibres regarded as potential materials for polymer composite based industries. Mechanical properties of kenaf fibre composite comparable to glass fibre composite. Kenaf composites nowadays used as construction materials for different buildings. Abstract: Kenaf regarded as an industrial crop in Malaysia and also grown commercially in other part of world for different applications. It is certainly one of the important plants cultivated for natural fibres globally, next to cotton, which is endemic to ancient Africa. It has great potential to use as automotive and construction materials due its long fibres derived from outer fibrous bark, the bast. Natural fibres such as kenaf getting attention of researchers and industries to utilize it in different polymer composites based products due to environmental awareness of consumers and government regulation in some countries. In many research studies, kenaf fibres are reinforced with polymer matrix to form fibre reinforced polymeric composites which perfectly improve the features of the polymers. Mechanical properties of kenaf fibres is comparable to existing materials and it will play an important role to utilize as the material of choice for a varied range of structural and non-structural industrial products with polymer matrix. The innumerable properties of kenaf fibres in original and reprocessed plastics are demonstrated by many recent studies and research efforts make it suitable construction materials (such as boards of different densities, breadths, along with fire and insect resistance). In this review work, we try to explore and highlights the previous work involving mechanical properties of kenaf fibre reinforced polymer composites to provide a perfect source of literature for doing further research in this topic to explore it as construction and building materials.